Leaving ideological groups behind: A model of disengagement. (4th May 2018) - Harris, K. J.; Gringart, E.; Drake, D.
ABSTRACT: The social mechanisms in ideological groups work to promote a cohesive social unit and present significant barriers to disengaging. Nonetheless, involvement in these groups is often not a lifelong commitment and many members do leave. The aim of this study was to explore the personal experience of the exiting process from a diverse range of ideological groups, and to construct a theory of disengagement, through 27 in-depth interviews with former members of 1% motorcycle clubs, military special operations forces, cults, white supremacists and fundamental religious or political groups. Participant interviews were analysed using grounded theory methodology to construct a model of disengagement. After the experience of an initial trigger, the group was perceived as inconsistent with the self-concept and conflicted with personally held goals and values, which threatened the participants' psychological integrity. Participants employed self-concept management strategies to address this inconsistency, which culminated in the decision to leave and tempering of ideology. These findings have relevance to social policies, which aim to influence membership in ideological groups.